Revisão integrativa sobre o conceito de trabalho em equipe na perspectiva da integralidade na atenção primária à saúde - Martins, Marlene Das Graças (2013)
The integrative review has been an important tool for research in the area of health knowledge since it allows the synthesis of research on a particular subject. The teamwork from the perspective of integrality, is among the most important topics to be discussed within the organization, operation and legislation of the current National Health Policy of the Unified Health System. The integrality is a guideline of UHS little addressed in health practices, although one of the major preconditions for the reorganization of the work process. So, the objective of this study was to conduct an integrative review of the literature about the concept and categories of analysis of teamwork in perspective for integrality in Primary Health Care The research encompassed the search and selection of national and international texts during the period from 2000 to 2011, in LILACS electronic databases, PubMed, SCIELO, CINAHL and legal documents, textbooks, dissertations, theses, in the printed version. We used the descriptors and keywords in Portuguese, English and Spanish, according to the criteria of inclusion and exclusion. We identified 2520 articles, which were performed in readings of titles and abstracts. Of these, 240 articles were selected for full reading that responded to the guiding question and ultimately included 52 publications. From the contributions of authors surveyed, it was found that there is no consensus about the concept of teamwork in health from the perspective of integrality, though this principle be a legal precept guaranteed constitutionally. We identified nine analytic categories which the most cited were communication, interaction and shared actions. This research also evidenced the need for a broad debate on this subject, which could justify the new challenges of knowing and of interdisciplinary doing for the consolidation of the principle of integrality in the Unified Health System.